EFEKTIVITAS MODEL PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR IPA SISWA KELAS IV MI DARUS SAKINAH TENGGARONG SEBRANG - Nadia Amanda; Marniati Kadir; Khusnul Khotimah; Nafla Maulida (Studies in Advanced Pedagogy and Academic Understanding, 2024)
This study aims to evaluate the effectiveness of the "everyone is a teacher here" instructional model on the learning outcomes of fourth-grade students in Natural Sciences at MI Darus Sakinah Tenggarong Seberang. The research method employs a quantitative experimental approach with a Pre-test Post-test Non Equivalent Control Group Design. The sample consists of 56 students, with class IV A as the experimental group and class IV B as the control group. Data were collected through observation, documentation, and tests, and analyzed using normality tests, homogeneity tests, N-Gain tests, and Independent Sample T-tests. The results of the study show a significant improvement in the learning outcomes of fourth-grade students in Natural Sciences who participated in this instructional model, with a mean posttest score of 85.00. The conclusion drawn from the Independent Sample T-test confirms that the "everyone is a teacher here" instructional model is significantly effective in improving the learning outcomes of fourth-grade students in Natural Sciences at MI Darus Sakinah Tenggarong Seberang.